2005
DOI: 10.1002/ijc.20588
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid induces apoptosis through mitochondrial intrinsic pathway and caspase-3 activation in M4Beu melanoma cells

Abstract: Over the coming years, skin cancer could become a significant public health problem. Previous results indicate that ursolic acid (UA), a pentacyclic triterpene acid, has pleiotropic biologic activities such as antiinflammatory and antiproliferative activities on cancer cells. As UA represents a promising chemical entity for the protection of human skin, in agreement with tests done by the cosmetic industry, we investigated its effects on the M4Beu human melanoma cell line. In this report, we demonstrated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 46 publications
2
79
1
3
Order By: Relevance
“…In those studies, we demonstrated for the first time that UA has a significant antiproliferative effect associated with the induction of the apoptotic process (14,15). In the literature, it is well established that the activation of the apoptotic transduction pathway is dependent on cell type and subcellular targets.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In those studies, we demonstrated for the first time that UA has a significant antiproliferative effect associated with the induction of the apoptotic process (14,15). In the literature, it is well established that the activation of the apoptotic transduction pathway is dependent on cell type and subcellular targets.…”
Section: Introductionmentioning
confidence: 64%
“…Western blot analysis was performed as previously described (15). Briefly, anti-Bax and anti-Bcl-2 were used at a dilution of 1:200, while anti-ß-actin was used at 1:5000 and horseradish-peroxidaselinked secondary antibody at 1:1000.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, their beneficial effects have been analysed by extensive preclinical and epidemiological studies [1][2][3][4]. Some natural triterpenoids such as oleanolic, betulinic and ursolic acids have shown notable effects in suppressing tumourigenesis as well as inhibiting tumours [1,[5][6][7][8][9]. Also, a range of newly developed synthetic triterpenoids are more potent than the naturally occurring parent structure [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…He and Liu first isolated and identified 20 pure compounds from cranberries, including UA and showed that these compounds have potent anti-proliferative activities against HepG2, liver cancer cells and MCF7, breast cancer cells [170]. In vitro, UA has been shown to induce apoptosis in a variety of tumor cells, including HL-60, human leukemia cancer cells [171,172], K562 [173], HEC108 and SCG-II, human endometrial cancer cells [174,175], M4Beu human melanoma cells [176], A549, human non-small cell lung cancer cells [177], PC-3 and LNCaP, human prostate cancer cells [178], HaCaT, human keratinocyte cells [179], human Burkitt's lymphoma Daudi cells [180] in a dose-and time-dependent manner. The major mechanisms by which UA induces apoptosis is through inhibition of DNA replication [171], caspases activation [181,182] inactivation of protein tyrosine kinases [183], and induction of Ca 2+ release [172,180].…”
Section: Ursolic Acid (Ua)mentioning
confidence: 99%